Evaluation of Piper aduncum Linn. Essential Oil (Fam:Piperaceae) against Periplaneta americana(L.) - I Ling A; S Sulaiman; H Othman (Tehran University of Medical Sciences, 2009)
Background: The efficacy of Piper aduncum essential oil was evaluated against Periplaneta americana adults and nymphs in the laboratory. Methods: The plant essential oil at varying concentrations ranging between 10,000 to 80,000 ppm were placed inside glass beakers, rolled horizontally to ensure the essential oil covers all sides of the beakers and exposed to adults and nymphs of P. americana. Resigen (R) 1ppm was used as positive control and distilled water as negative control. The LT50 and LT90 was obtained using Log Probit programme. Results: Exposure of essential oil to females P. americana at concentrations between 10,000 to 80,000 ppm indicated the LT50 and LT90 values between 5.31 h-189.19 h and 14.90 h-2105.31 h, respectively. Treatment with the same concentrations against males P. americana ,the LT50 and LT90 were 2.08 h-181.73 h and 5.4 h-8460.51 h, respectively. Treatment against the nymphal stage with the same range of concentrations indicated the LT50 and LT 90 of 4.68 h-381.02 h and 28.71 h-5313.36 h, respectively.The nymphs and males were more susceptible than the females cockroaches. Treatment with Resigen (R) at 1ppm indicated much lower LT 50 and LT 90 values of 2.54 h-9.47 h for the females, 1.47 h-4.22 h for the males and 4.69 h-8.92 h for the nymphs.The negative control indicated no mortality for all stages of the cockroach. Conclusion: Piper aduncum essential oil can be used as an alternative natural product for controlling the cockroach Peripatetic americana.